2015
DOI: 10.1088/1748-0221/10/05/c05009
|View full text |Cite
|
Sign up to set email alerts
|

1-Grad total dose evaluation of 65 nm CMOS technology for the HL-LHC upgrades

Abstract: The radiation tolerance of 65 nm bulk CMOS devices was investigated using 10 keV X-rays up to a Total Ionizing Dose (TID) of 1 Grad. Irradiation tests were performed at room temperature (25 • C) as well as at low temperature (−15 • C). The implications on the DC performance of n and p channel transistors are presented. For small size devices, a strong performance degradation is observed from a dose of 100 Mrad. Irradiations made at room temperature up to 1 Grad show a complete drive loss in PMOS devices, due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 7 publications
3
42
0
Order By: Relevance
“…In a second step, annealing at 100 • C was performed and measured after 4 and 24 hours. The annealing was performed with the circuit biased in normal operating conditions, which has the most damaging effect [21]. The second sample was irradiated up to 600 Mrad and measured after 24 hours room temperature annealing and 24 hours annealing at 100…”
Section: Tid Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a second step, annealing at 100 • C was performed and measured after 4 and 24 hours. The annealing was performed with the circuit biased in normal operating conditions, which has the most damaging effect [21]. The second sample was irradiated up to 600 Mrad and measured after 24 hours room temperature annealing and 24 hours annealing at 100…”
Section: Tid Irradiationmentioning
confidence: 99%
“…Compared to the LC-oscillator, a large annealing effect is observed. According to [21], this is due to the short-channel devices in the cells for which the effects are triggered after high-temperature annealing. The large variation in tuning characteristics caused the PLL to be unable to lock after being irradiated to 600 Mrad since the oscillator could no longer run at 2.56 GHz.…”
Section: B Ring Oscillatormentioning
confidence: 99%
“…X-rays provide a good way to compare old with new data, even though very long exposure times are needed to reach TID levels up to 1 Grad: a review of the results can be found in [16]. The results show significant degradation above 100 Mrad, particularly in core minimum size pMOSFETs.…”
Section: Radiation Effectsmentioning
confidence: 99%
“…Simulations show that its pixel detectors will integrate a fluence (1 MeV neutron equivalent) of about 10 16 n/cm 2 and a Total Ionizing Dose (TID) of 10 MGy (1 Grad). The radiation damage on the proposed 65 nm technology, due to both total dose and single event effects, has been studied by the RD53 Radiation Working Group [3]. Tests were done on single transistors with different geometries.…”
Section: Radiation Hardnessmentioning
confidence: 99%